Does relative grading help male students? Evidence from a field experiment in the classroom. (April 2020) - Czibor, Eszter; Onderstal, Sander; Sloof, Randolph; van Praag, C. Mirjam
Abstract: We conduct a framed field experiment at a Dutch university to compare student effort provision and exam performance under the two most prevalent evaluation practices: absolute (criterion-referenced) and relative (norm-referenced) grading. We hypothesize that the rank-order tournament created by relative grading will increase effort provision and performance among students with competitive preferences. We use student gender and survey measures (self-reported as well as incentivized) as proxies for competitiveness. Contrary to our expectations, we find no significant impact of relative grading on preparation behavior or exam scores, neither among men nor among students with higher measures of competitiveness. We discuss several potential explanations for this finding, and argue that it is likely attributable to the low value that students in our sample attach to academic excellence.